Cardiovascular impact of intravenous caffeine in preterm infants. (23rd May 2018) - Huvanandana, Jacqueline; Thamrin, Cindy; McEwan, Alistair L.; Hinder, Murray; Tracy, Mark B.
Abstract: Aim: To evaluate the acute effect of intravenous caffeine on heart rate and blood pressure variability in preterm infants. Methods: We extracted and compared linear and nonlinear features of heart rate and blood pressure variability at two time points: prior to and in the two hours following a loading dose of 10 mg/kg caffeine base. Results: We studied 31 preterm infants with arterial blood pressure data and 25 with electrocardiogram data, and compared extracted features prior to and following caffeine administration. We observed a reduction in both scaling exponents (α1, α2 ) of mean arterial pressure from detrended fluctuation analysis and an increase in the ratio of short‐ (SD1) and long‐term (SD2) variability from Poincare analysis (SD1/SD2). Heart rate variability analyses showed a reduction in α1 (mean (SD) of 0.92 (0.21) to 0.86 (0.21), p < 0.01), consistent with increased vagal tone. Following caffeine, beat‐to‐beat pulse pressure variability (SD) also increased (2.1 (0.64) to 2.5 (0.65) mmHg, p < 0.01). Conclusion: This study highlights potential elevation in autonomic nervous system responsiveness following caffeine administration reflected in both heart rate and blood pressure systems. The observed increase in pulse pressure variability may have implications for caffeine administration to infants with potentially impaired cerebral autoregulation.